Automated People Movers and Automated Transit Systems 2022 - Sproule, William J. (American Society of Civil Engineers, 2022)
This collection contains 9 peer-reviewed papers on automated transportation systems presented at the 18thInternational Conference on Automated People Movers and Automated Transit Systems, held in Seattle, Washington, May 31-June 3, 2022.